(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the theoretical and practical aspects of game methods in teaching English in the educational process of the university. The psychological and pedagogical literature on the theory of the occurrence of the game presented in the works of K. Livingstone, K.D. Ushinskiy, D. B. Elkonin, M.F. Stronin, L.S. Vygotsky and others are analyzed. The functions of game methods are revealed: educating, pedagogical, entertaining, communicative, relaxation, psychological developing. The methodology of using game methods in teaching English is described supported by specific examples.